Sovereign Bonds and Socially Responsible Investment - Drut, Bastien (Journal of business ethics, 2010)
This article investigates how the mean–variance efficient frontier defined by sovereign bonds of 20 developed countries is affected by the consideration of socially responsible indicators for countries in investment decision-making. For a global rating of socially responsible performances, we show that it is possible to build portfolios with an increased average rating without significantly harming the risk/return relationship. This result differs when considering sub-ratings related to the environment, social concerns and public governance. The results are good news for responsible investors and suggest that socially responsible portfolios of sovereign bonds can be built without a significant loss of mean–variance efficiency.